Studi Kasus: Peran Orang Tua dalam Pendidikan Inklusi di Sekolah Dasar Seruma - Kristi Wardani; Siti Irene Dwiningrum (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
This qualitative research with case studies aims to analyze the role of parents in inclusive education at SD SERUMA Sleman. This type of research is qualitative with a case study design. In accordance with the research design, the subject was Seruma Elementary School in Sleman Regency. Collecting data using interview and documentation techniques. The validity of the data was done by confirming the results of observations and interview documents. The data credibility test is done by extending observations, increasing persistence, and references. The results showed that the role of parents in inclusive education is implemented in a participatory and collaborative manner. The positive role of parents can have a strong influence on the implementation of inclusive schools. These results indicate that the role of parents and schools and teachers to be involved in the process of implementing inclusive education is very supportive of the creation of better and meaningful inclusive learning.